Conserved Bacterial-Binding Peptides of the Scavenger-Like Human Lymphocyte Receptor CD6 Protect From Mouse Experimental Sepsis - Martínez-Florensa, Mario; Català, Cristina; Velasco-de Andrés, María; Cañadas, Olga; Fraile-Ágreda, Víctor; Casadó-Llombart, Sergi; Armiger-Borràs, Noelia; Consuegra-Fernández, Marta; Casals, Cristina; Lozano, Francisco (Frontiers in Immunology, 2018)
Sepsis is an unmet clinical need constituting one of most important causes of death world-wide, a fact aggravated by the appearance of multi-drug resistant (MDR) strains due to indiscriminate use of antibiotics. Host innate immune receptors involved in pathogen-associated molecular patterns (PAMPs) recognition represent a source of broad-spectrum therapies alternative or adjunctive to antibiotics. Among the few members of the ancient and highly conserved Scavenger Receptor Cysteine-Rich superfamily (SRCR-SF) sharing bacterial-binding properties there is CD6, a lymphocyte-specific surface receptor. Here, we analyze the bacterial-binding properties of three conserved short peptides (11-mer) mapping at extracellular SRCR domains of human CD6 (CD6.PD1, GTVEVRLEASW; CD6.PD2 GRVEMLEHGEW; CD6.PD3, GQVEVHFRGVW). All peptides show high binding affinity for PAMPs from Gram-negative (lipopolysaccharide; Kd from 3.5 to 3000 nM) and Gram-positive (lipotheichoic acid; Kd from 36 to 680 nM) bacteria. The CD6.PD3 peptide possesses broad bacterial-agglutination properties, and improved survival of mice undergoing polymicrobial sepsis in a dose- and time-dependent manner. Accordingly, CD6.PD3 triggers a decrease in serum levels of both pro-inflammatory cytokines and bacterial load. Interestingly, CD6.PD3 shows additive survival effects on septic mice when combined with Imipenem/Cilastatin. These results illustrate the therapeutic potential of peptides retaining the bacterial-binding properties of native CD6.